Brain vascular intima vulnerability among Human Immunodeficiency Virus positive and negative individuals - HUNTER, Madeleine D (AIDS, 2018)
OBJECTIVE: To test whether HIV is associated with brain large artery vulnerable intima. DESIGN: Cross-sectional study of autopsied HIV+ cases sex- and age-matched to HIV-controls. METHODS: Brain large arteries from 302 autopsied cases (50% HIV+) were evaluated morphometrically for the presence of atherosclerosis, size of necrotic core and fibrous cap thickness. Intima vulnerability was measured as intima elastolytic score (0–5, based on intimal metalloproteinases [MMP]-2, −3, and −9 and tissue inhibitor for (MMP) −1 and −2 staining), intima inflammatory score (0–3, based on intimal presence of CD3+ and CD68+ cells and TNF⍺ staining), neoangiogenesis (Factor VIII staining), and apoptosis (caspase 3 staining). Hierarchical generalized linear models were used to obtain the beta estimates and their 95% confidence intervals, adjusting for demographics and vascular risk factors. RESLUTS: The prevalence of atherosclerosis did not differ by HIV status. Necrotic cores filled larger proportions of the intima in HIV+ individuals with CD4 count >200 at death compared to HIV-controls (adjusted B=11.6%, P=0.04). HIV+ individuals had greater elastolytic scores (adjusted B= 0.34; P=0.02), especially those with < 200 CD4+ cells/μl at death (adjusted B= 0.41; P=0.01). Intima inflammation, neoangiogenesis, and apoptosis were not different among HIV+ cases versus HIV-controls. CONCLUSION: Individuals with HIV and CD4 ≥ 200 at death had relatively larger necrotic cores while those with HIV and CD4 < 200 at death had evidence of increased connective tissue remodeling in the intima. These findings suggest an increased potential for endothelial erosion, thrombosis, and plaque rupture that may relate to higher risk for vascular events.